Wind tunnel testing of a full scale helicopter blade section with an upstream active Gurney flap - Loendersloot, R.; Freire Gómez, J.; Booker, J.D. (My University, 2014)
Wind tunnel tests were performed on an aerofoil section comparable to that of a full scale helicopter blade section with an upstream active Gurney flap in the framework of the European project CleanSky ITD Green RotorCraft. A modified NACA0012 profile was used, with 23 Kulite pressure transducers embedded in the profile’s surface and with an integrated actuator system for the Gurney flap. The Gurney flap, positioned at 95% of the chord length and with a deployed size of 1.3% of the chord length, extended the full span width of the section. The aerofoil was supported by a mounting system with automated control of the angle of attack. The effect of the Gurney flap is assessed for various deployment strategies. The test campaign carried out was successful. The aerodynamic behaviour can be extracted from the data and contains valuable information for validation of 2D numerical models developed by other partners in the project. The most important improvement of the setup for future use is the stabilisation of the inclinometer readings, which showed a significant amount of noise.